GROUNDWATER CONTAMINATION RISK ASSESSMENT:A CASE STUDY OF THE HAT YAI BASIN - Nantiya, Riyapan (Prince of Songkla University, Faculty of Engineering Hat Yai, Songkhla, Thailand, 2016)
For decades, Hat Yai city, a major city in southern Thailand, has experienced significant increase in population, urbanization and industrialization which leads to major concerns of over utilization of groundwater and potential of groundwater contamination. An objective of this study was to conduct groundwater contamination risk assessment for the Hat Yai basin area. Hazard Ranking System was used for assessing contaminant potential and DRASTIC method was used to determine aquifer vulnerability. Risk index of groundwater contamination was defined by a product of contaminant potential and aquifer vulnerability. Based on the results of this study, the risk index of groundwater contamination was found to be 4 out of 25 which indicated that, for the Hat Yai basin , in general, there was very low risk of groundwater contamination.